2016
DOI: 10.1016/j.renene.2016.01.082
|View full text |Cite
|
Sign up to set email alerts
|

Microbial electrolysis contribution to anaerobic digestion of waste activated sludge, leading to accelerated methane production

Abstract: 14Methane production rate (MPR) in waste activated sludge (WAS) digestion processes is typically limited 15 by the initial steps of complex organic matter degradation, leading to a limited MPR due to sludge 16 fermentation speed of solid particles. In this study, a novel microbial electrolysis AD reactor (ME-AD) was 17 used to accelerate methane production for energy recovery from WAS. Carbon bioconversion was 18 accelerated by ME producing H 2 at the cathode. MPR was enhanced to 91.8 gCH 4 /m 3 reactor/d in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 31 publications
4
66
0
Order By: Relevance
“…This revealed that the electroactive biofilm formed on the electrode surface must have enhanced the stability of the AD rather than the electrical current (De Vrieze et al, 2014). Similarly, Liu et al (2016) combined MEC and AD to form an MEC-AD system to improve CH4 production rate (MPR) from waste activated sludge. MPR was enhanced to 91.8 g CH4/m 3 reactor/d in the integrated MEC-AD reactor, compared to 30.6 g CH4/m 3 reactor/d in the AD alone .…”
Section: Integration Of Mec With Anaerobic Digestion (Ad)mentioning
confidence: 99%
“…This revealed that the electroactive biofilm formed on the electrode surface must have enhanced the stability of the AD rather than the electrical current (De Vrieze et al, 2014). Similarly, Liu et al (2016) combined MEC and AD to form an MEC-AD system to improve CH4 production rate (MPR) from waste activated sludge. MPR was enhanced to 91.8 g CH4/m 3 reactor/d in the integrated MEC-AD reactor, compared to 30.6 g CH4/m 3 reactor/d in the AD alone .…”
Section: Integration Of Mec With Anaerobic Digestion (Ad)mentioning
confidence: 99%
“…fabricated a three‐dimensional biphasic Ni 5 P 4 ‐NiP 2 nanosheet matrix to act as a cathodic tunnel for H 2 generation in a microbially catalyzed bioanode, and obtained a high H 2 production rate of 9.78 mL day −1 cm −2 . In the past decade, Pt covered carbon cloth has been widely applied as cathode catalyst in MECs, but it is difficult to apply in practical H 2 production due to its high cost and the lack of strength of the carbon cloth. Nickel foam with Pt as the catalyst promoted H 2 yield to 0.71 m 3 m −3 day −1 under the applied supply of 0.8 V .…”
Section: Applications Of the Microbial Electrolysis Cellmentioning
confidence: 99%
“…The effect of the applied voltage on the enhancement of CH 4 production in five studies: R1, R2, R3, R4 and R5, which tested different types of organic matter as a substrate. R OC (open‐circuit), R CC (closed‐circuit, 0.8 V), and WAS (waste‐activated sludge).…”
Section: Research Advancesmentioning
confidence: 99%
“…Lately, the contribution of bacteria without the ability for anode respiration in bioelectrochemical systems has been discussed. It was found that the part of the microbial communities that did not participate in extracellular electron transfer was maintained in the anaerobic niche of electrode biofilms, where they could provide labile products for electrode-respiring bacteria (Liu et al, 2016a(Liu et al, , 2016b. The diversity of the community may be maintained through utilization of compounds excreted by electrogenic bacteria, or by growth on the biomass of other cells by nonacetate-utilizing bacteria (Liu et al, 2010).…”
Section: Microbiological Identification Of Dominant Strain In Mixed-cmentioning
confidence: 99%